TP9.2.30Sigmoid Volvulus: Is a More Aggressive Approach Justified? Results of a Retrospective Cohort Study. (28th October 2021) - Slack, Zoe; Shams, Mohamed; Sallam, Mahmoud; Bond-Smith, Giles; Tebala, Giovanni
Abstract: Aims: Sigmoid volvulus is a common cause of emergency surgical admission. It often affects older males who are institutionalised and are less suitable surgical candidates. Definitive treatment is surgical but first line treatment is via endoscopic devolution with or without placement of a rectal tube. After non-operative management recurrence is likely and carries a high mortality, therefore an early surgical approach may be considered in patients who are fit for surgery. We have retrospectively analysed a cohort of patients with sigmoid volvulus in order to clarify if and when a more aggressive management is indicated. Methods: We have reviewed data on admitted patients diagnosed with sigmoid volvulus over a 2-year period. Demographic, clinical data, morbidity and mortality were recorded in a database. Analysis was carried out with statistical programs. The primary endpoint was patient survival. Secondary endpoint was the estimation of the factors that condition surgical choice. Results: We analysed 78 cases. 74.4% had multiple admissions and recurrences. 39.7% of patients underwent surgical resection. The average survival was 54.9±8.8 months from the first hospitalisation, irrespective of the treatment. Long-term survival was positively influenced by being female, having a low "social score", a younger age and surgery. Multivariate analysis showed that only being female and surgery were independently associated with better survival. Conclusions: In conclusion, we believe that early surgery may be the best approach in patients with recurrent sigmoid volvulus, as it ensures longer survival with a better quality of life, regardless of the patient's social and functional condition.